Modeling roles of service recovery strategy: A relationship-focused view - Ok, Chihyung; Shanklin, Carol W.; Back, Ki-Joon (My University, 2008)
This study proposed and tested a theoretical model consisting of antecedents and consequences of recovery satisfaction using scenario experimentation with three dimensions of justice manipulated at two levels each (2x2x2 factorial design). Each participant was provided the same service failure (overcooked steak) scenario and one of the eight recovery scenarios (a combination of dimensions of justice). Structural equation modeling was used to test the hypotheses based on 286 cases. All three dimensions of justice had positive effects on recovery satisfaction. Recovery satisfaction had positive effects on trust and overall satisfaction. Trust had positive effects on commitment and overall satisfaction. Commitment had positive effects on overall satisfaction and behavioral intentions. Although a service failure might negatively affect customers' relationship with the service provider, effective recovery can reinforce attitudinal and behavioral outcomes. The study findings emphasized that recovery efforts should be viewed not only as a strategy to recover immediate satisfaction but also as a relationship tool to build long-term relationships with customers.
Keywords: Service recovery; Justice theory; Recovery satisfaction; Trust and commitment; Overall satisfaction; Behavioral intentions